Microalgae: towards human health from urban areas to space missions - Xie, Xiulan; Jaleel, Abdul; Zhan, Jiasui; Ren, Maozhi (Frontiers in Plant Science, 2024)
Space exploration and interstellar migration are important strategies for long-term human survival. However, extreme environmental conditions, such as space radiation and microgravity, can cause adverse effects, including DNA damage, cerebrovascular disease, osteoporosis, and muscle atrophy, which would require prophylactic and remedial treatment en route. Production of oral drugs in situ is therefore critical for interstellar travel and can be achieved through industrial production utilizing microalgae, which offers high production efficiency, edibility, resource minimization, adaptability, stress tolerance, and genetic manipulation ease. Synthetic biological techniques using microalgae as a chassis offer several advantages in producing natural products, including availability of biosynthetic precursors, potential for synthesizing natural metabolites, superior quality and efficiency, environmental protection, and sustainable development. This article explores the advantages of bioproduction from microalgal chassis using synthetic biological techniques, suitability of microalgal bioreactor-based cell factories for producing value-added natural metabolites, and prospects and applications of microalgae in interstellar travel.